CAMP (C13orf8, ZNF828) is a novel regulator of kinetochore–microtubule attachment - Itoh, Go (Nature Publishing Group, 2011)
Proper attachment of microtubules to kinetochores is essential for accurate chromosome segregation. Here, we report a novel protein involved in kinetochore–microtubule attachment, chromosome alignment-maintaining phosphoprotein (CAMP) (C13orf8, ZNF828). CAMP is a zinc-finger protein containing three characteristic repeat motifs termed the WK, SPE, and FPE motifs. CAMP localizes to chromosomes and the spindle including kinetochores, and undergoes CDK1-dependent phosphorylation at multiple sites during mitosis. CAMP-depleted cells showed severe chromosome misalignment, which was associated with the poor resistance of K-fibres to the tension exerted upon establishment of sister kinetochore bi-orientation. We found that the FPE region, which is responsible for spindle and kinetochore localization, is essential for proper chromosome alignment. The C-terminal region containing the zinc-finger domains negatively regulates chromosome alignment, and phosphorylation in the FPE region counteracts this regulation. Kinetochore localization of CENP-E and CENP-F was affected by CAMP depletion, and by expressing CAMP mutants that cannot functionally rescue CAMP depletion, placing CENP-E and CENP-F as downstream effectors of CAMP. These data suggest that CAMP is required for maintaining kinetochore–microtubule attachment during bi-orientation.